Interleukin-6 and disease activity in childhood systemic lupus erythematosus - Satria, Cahya Dewi; Kurniati, Nia; Muktiarti, Dina (Paediatrica Indonesiana, 2023)
Background Systemic lupus erythematosus (SLE) is a complex disease with various manifestations. Interleukin-6 (IL-6) is a pleiotropic cytokine with a wide range of biological activities which plays an important role in immune regulation and inflammation. Serum level of IL-6 may be used as a parameter of disease activity, especially in pediatric SLE patients with mild disease activity or total remission with conflicting clinical manifestations and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) scores. Objective To identify the characteristics of serum IL-6 concentration in pediatric SLE with mild disease activities and total remission. Methods This case-control study was performed at the allergy-immunology outpatient clinic, Department of Child Health Dr. Cipto Mangunkusumo Hospital, Jakarta and Dr. Sardjito Hospital, Yogyakarta. Serum IL-6 concentration and disease activity were assessed in all pediatric SLE patients aged 1-18 years old. Disease activity was assessed with SLEDAI scores and serum level of IL-6 was measured by enzyme-linked immunosorbent assay. Results Among 60 subjects included in this study, 30 subjects with mild activities were in the case group and 30 subjects with total remissions were in the control group. There was no difference in serum IL-6 concentration between the case and control group (OR 0.483; 95%CI 0.041to 5.628; P=0.500). In this study, 2 subjects with urinary tract infection had high serum IL-6 concentrations. Conclusion There is no difference in serum IL-6 concentration between pediatric SLE patients with mild disease activities compared to total remissions.